Antibiotic self-medication-prevalence and trends among adults attending an urban health centre in South Kerala - Mohanlal, Jathavedus; Eliza, Sharon Raj; Nair, Aswathi; Anilkumar, Angitha (International Journal Of Community Medicine And Public Health, 2022)
Background: Antibiotics acts as an essential tool, especially in the developing world where infectious diseases are the major cause of mortality. But widespread inappropriate use of antibiotics has been identified as the major reason for antimicrobial resistance. Objectives were to estimate the prevalence of antibiotic self-medication among adults attending an urban health centre in South Kerala and to assess the trends of antibiotic self-medication in the study group Methods: This cross-sectional study was conducted among community dwelling adults attending the health centre which covers the urban field practice area of Pushpagiri institute of medical sciences, Tiruvalla. Data was collected using interviewer administered questionnaire from adults aged 18 years and above using consecutive sampling method Results: Out of 236 participants, 138(58.5%) were females and 98 (41.8%) males. The mean age of the study population was 50.10±18.27 SD. Overall prevalence of antibiotic self-medication among the study group was 12.7%. In our study, age group (p<0.001), education (p<0.001) and socio-economic status (p<001) were significantly associated with antibiotic self-medication. The most common drug among study population was azithromycin (66.7%). Conclusions: Even though the overall prevalence of antibiotic self-medication was low among community dwelling adults in South Kerala, higher rates were seen in a certain stratum of the population. The study necessitates the need for better understanding of the effects of antibiotic self-medication which can be done through effective strategies like behavior change communication and promoting further research into the cause and effects of antibiotic self-medication